Vocational education and training in Cyprus : short description - (:unkn) unknown (Publications Office of the European Union, 2012)
This overview of the vocational education and training system in Cyprus is published during the Cypriot Presidency of the Council of the EU (second half of 2012). It forms part of the series of short descriptions regularly published by Cedefop on national VET systems. "The VET system of Cyprus is playing a significant role in dealing with the adverse effects of the economic crisis on the labour market and in laying the foundations for future development. To continue to fulfil the expectations of the Cypriot economy and society, VET is undergoing essential reforms. The structure of VET is being transformed by the introduction of a new modern apprenticeship, an alternative pathway for young people between 14 and 20, and the establishment of post-secondary institutes for technical and vocational education and training, which will offer students an intermediate level of education. The implementation of the new modern apprenticeship has begun and it will become fully operational by 2015. Secondary technical and vocational education provides a broad range of initial training programmes in Cyprus. Its new curricula, expected to be developed by 2015, will enhance the attractiveness of VET and match specialisations with the current needs of the labour market. VET is an important part of and features prominently in the Cyprus lifelong learning strategy. Its main actions include the enhancement of lifelong guidance and counselling services, and the development of a national qualifications framework (NQF)." (Autorenreferat, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; I 2.2.2 Osteuropa; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Berufliche Weiterbildung; Bildungsberatung; Berufsberatung; Zypern